Initial Development of Instructional Video as the Development of Environmental Literacy - Arifani, Risti Putri; Putra, M. Jaya Adi; Alpusari, Mahmud; Antosa, Zariul (Proceedings of the UR International Conference on Educational Sciences, 2018)
The ability of each individual to behave using his understanding of environmental conditions such as taking decisions related to the environment is important to be understood by each student.This ability is often referred to as environmental literacy. This research is the development of an initial development learning video to train students to make decisions according to their understanding of the environment.This video was developed through the Decision Making Cooperative learning procedure.The initial process of developing this video by creating scripts that are adapted to learning competencies is understanding environmental conditions that affect health, and efforts to maintain environmental health. Several videos are selected that are suitable for learning conditions.Student activity settings are also included in the video including conditions that encourage students to draw conclusions.There are a number of inputs provided by the validation team to improve the videos, among others related to the setting of problems that will be used as material for discussion for students. The initial results of the development of this video show that this video can be tested on students.